1995
DOI: 10.1161/01.cir.91.2.403
|View full text |Cite
|
Sign up to set email alerts
|

SC-54684A: An Orally Active Inhibitor of Platelet Aggregation

Abstract: SC-54684A, an orally active antiplatelet drug now in clinical trial, is shown to be a potent, specific fibrinogen binding inhibitor that blocks platelet aggregation to a wide variety of known stimuli and has good bioavailability in animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 26 publications
0
30
0
1
Order By: Relevance
“…The active moiety of xemilofiban is a potent, specific inhibitor of fibrinogen binding that blocks platelet aggregation to all known stimuli. 3 A previous study demonstrated that administration of xemilofiban to conscious dogs resulted in dose-dependent antiplatelet activity and a high level of bioavailability. 10 In this report, we assessed for the first time the antithrombotic effectiveness of orally administered xemilofiban or xemilofiban with ASA in a canine model of coronary artery thrombosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The active moiety of xemilofiban is a potent, specific inhibitor of fibrinogen binding that blocks platelet aggregation to all known stimuli. 3 A previous study demonstrated that administration of xemilofiban to conscious dogs resulted in dose-dependent antiplatelet activity and a high level of bioavailability. 10 In this report, we assessed for the first time the antithrombotic effectiveness of orally administered xemilofiban or xemilofiban with ASA in a canine model of coronary artery thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrochloride salt (SC-54701A) of the active moiety of xemilofiban is a potent inhibitor of fibrinogen binding to platelets. 3 This compound is highly selective for the GP IIb/IIIa receptor compared with other integrins sharing the same ␤ 3 -subunit. 3 ASA is the most convenient and widely tested antiplatelet agent, but this drug possesses limited antithrombotic efficacy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nicholson et al [1995] reported that the bioavailability of SC-54684A in dogs was 21.3%. Furthermore, YM128 showed good availability (22.2%) in cynomolgus monkeys also.…”
Section: Oral Route Ym128mentioning
confidence: 99%
“…This compared very favorably with the oral systemic availability of other oral GP IIb/IIIa inhibitors that entered development, which ranged from 9 to 25%. 32,54,55 Another favorable pharmacokinetic parameter that made orbo®ban attractive for long-term use was its relatively long half-life of 18 hr in dogs, which made a twice-daily dosing regimen feasible. …”
Section: P R E C L I N I C a L P H A R M A C O L O G Ymentioning
confidence: 99%